Pembinaan Program Tahsin Al-Qur’an dalam Meningkatkan Potensi Menghafal Al-Quran Remaja Masjid Babussalam Pahlawan Belui - Sarbaini, Sarbaini; Kustati, Martin; Amelia, Rezki (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
Based on findings in the Babussalam Pahlawan Belui Mosque area, it was found that many teenagers did not understand how to read at all . The aim of this research is to implement a program that focuses on improving the Al-Quran reading skills of mosque teenagers . Based on the findings in the Babussalam Pahlawan Belui Mosque area, it was found that many teenagers did not understand how to read the Al-Quran properly and correctly, which has encouraged the service team to implement a program that focuses on improving the Al-Quran reading skills of Mosque Teenagers. Therefore, a special Tahsin program for teenagers was formed at the Babussalam Pahlawan Belui Mosque. The method for implementing the Tahsin and Tahfidz program is carried out by: (1) Identifying the ability to read the Al-Quran in Babussalam Mosque teenagers. (2) arranging the implementation of the presentation of makhraj, tajwid and tahsin material, (3) Implementing the Tahsin and Tahfidz programs. (4) Carry out an evaluation of the Tahsin and Tahfidz programs. coaching Results In practice, the Tahsin program is implemented by teaching makhraj, tajwid, tartil material which aims to improve the reading of the Al-Qur'an.